Social Media Marketing and Visitor Attraction in a Local Culinary Tourism Destination: A Case Study of Omah Kebon - Windra Ardhanu; Didik Haryadi Santoso (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2026)
This study examines Omah Kebon’s social media marketing strategy in enhancing visitor attraction as a local culinary tourism destination. Using a descriptive qualitative approach, data were collected through semi-structured interviews, three months of social media observation from August to October 2025, and documentation of 30 selected social media contents consisting of 15 feed posts, 10 reels, and 5 Instagram stories. The data were analyzed based on five social media marketing elements adapted from Tuten and Solomon’s framework: content strategy, engagement strategy, visual interaction, posting frequency, and user-generated content. The findings show that Omah Kebon relies strongly on visual content featuring the venue’s atmosphere, aesthetic photo spots, menus, services, facilities, and visitor activities to shape destination image and attract audience attention. Engagement is developed through reposting visitor stories, responding to comments and direct messages, collaborating with local influencers, and offering promotional discounts. Omah Kebon also maintains a relatively regular posting frequency of three to five posts per week, while visitor stories are reposted almost daily. However, its strategy remains largely attention-driven and faces several challenges, including limited human resources, inconsistent content planning, the absence of a structured content calendar, and lack of systematic performance evaluation of influencer and user-generated content. This study contributes to the understanding of social media marketing in local tourism MSMEs by showing how visual representation, digital interaction, and audience participation shape visitor attraction in local culinary tourism.